LE DIAGNOSTIC RELATIONNEL DE L’UNIVERSITÉ ET DE L’ENTREPRISE EN CÔTE D’IVOIRE: LES ENJEUX DU DÉVELOPPEMENT - Bouabre Gnoka Modeste (European Scientific Journal, ESJ, 2015)
The implementation report of the company and the university, in a functional and structural dynamics orchestrated product technical progress and economic and social growth. Permanence and continuity of the past (the technical progress and economic and social growth) reflect the real issues of development. What then can we expect, project operating in diagnostic perspective, interest report involving the universities and industry in Ivory Coast? How can we therefore assess the development through, forming a couple of these institutions? To what extent, in this situation, the collaboration between the university and the company prepares the conditions for development? The warm welcome of these questions, invites us to build our joint around the review of the work, the objectives of our study on the assumptions and methodology. Indeed, the study's overall objective to attract the attention of the competent authorities on the need to build lasting relationships and utilities from the perspective of development between the university, the company and the state in Ivory Coast. This study, then, three specific objectives: First, raise early warning of the university authorities in the development of fitness training courses to the needs of countries and companies; Second, encourage taking a political decision to associate the company and the university in a dynamic development for graduate training until their insertion into the professional fabric; and thirdly; cause the implementation of effective action for development through the binomial University-company. The methodology was based on the qualitative survey method through semi-structured interviews, by placing individual and focus group; with use of the interview guide administered to 75 people including teacher-researchers, researchers, administrators, students, employment specialists and campany leaders. We were able to meet today in Ivory Coast, the company wants a structured human organization and finalized taking economic and social functions of production, distribution of goods or services. As for the university, it has long carried the burden of a higher education organization based on values recognized as legitimate and central to society. The relational diagnosis between the university and the company allows us to note several points of convergence and especially of complementarity, necessary and essential, to found a strong couple and an accomplice who can work decisively not only in their mutual progress, but also and especially for the development of Côte d'Ivoire in its entirety